Bahasa BAHASA EMOSI DAN NASIHAT ORANG TUA:KAJIAN ANTROPOLINGUISTIK - Luna Simatupang; Mhd Haikal Ananta; Nova R. Siregar; Ida Basaria (LP2M UIN Abdul Muthalib Sangadji Ambon, 2026)
This study aims to analyze emotional expressions in parental advice to children through an anthropolinguistic and pragmatic approach. This research is motivated by the limited studies that discuss the relationship between speech forms, politeness strategies, implicature, emotional expression, and cultural values in Indonesian family communication. The study uses a descriptive qualitative approach involving 5 parents and 5 children as research informants. The research data consist of 15 parental advice utterances obtained through non-participant observation, semi-structured interviews, documentation, and recordings of family interactions. The data were analyzed through stages of data reduction, classification of speech forms, pragmatic interpretation, and drawing conclusions using Duranti's anthropolinguistic theory, Wierzbicka's language of emotion theory, Brown and Levinson's politeness theory, and Searle's speech act theory. Research results show that parental advice speech contains emotional expressions in the form of affection, hope, concern, anger, care, appreciation, and disappointment, which are realized through both direct and indirect speech. Negative emotions tend to be conveyed through negative politeness strategies and implicature to maintain harmony in interpersonal relationships within the family. This study shows that language in family communication not only functions as a tool for conveying moral messages, but also as a representation of cultural values, emotion regulation, and social practices of Indonesian society. Thus, this study contributes to the development of antrolinguistic and pragmatic research on the relationship between language, emotion, and culture in family communication.